PENGARUH FASIITAS TERHADAP KEPUASAN PELANGGAN (STUDI KAFE KULEA SPACE SUKARAME, BANDAR LAMPUNG) - Fadlul Akbar, Ahmad; Femmya Angel, Wila Bayu; Kurna Sandi, Ary (Faculty of economcs Universitas Singaperbangsa Karawang, 2022)
This study aims to determine the effect of facilities on customer satisfaction. The population of this study were consumers of the kulea space cafe Sukarame Bandar Lampung. The sample taken in this study amounted to 81 people. This research was conducted using a quantitative approach. Collecting research data using a questionnaire. The sampling technique used probability sampling method, specifically simple random sampling technique. The analysis used in this study is SEMPLS with SmartPLS 4 software. Based on the results of the analysis, it shows that there is a positive and significant effect on the effect of facilities on customer satisfaction. This means that facilities have an interrelated impact in influencing customer satisfaction. Facilities have a significant positive effect on customer satisfaction at the kulea space cafe Sukarame Bandar Lampung.